The protective effect of walnut (tetracarpidium conophorum) leaf and onion (allium cepa) bulb residues on the experimental pseudomonas aeruginosa infection in clarias gariepinus juveniles (2012)
The study assessed the effect of Walnut Leaf (WL) and Onion Bulb (OB) residues on disease resistance of Clarias gariepinus juveniles against infection with the bacteria pathogen Pseudomonas aeruginosa. Clarias gariepinus juveniles were fed with diets containing 0 (control), OB2 (0.5%), OB3 (1.0%), OB4 (1.5%), OB5 (2.0%), WL6 (0.5%), WL7 (1.0%), WL8 (1.5%) and WL9 (2.0%). Biochemical (serum total protein, albumin, globulin, albumin: globulin ratio) and haematological indices of the fish were investigated. Fish were exposed to 0.5ml of 107 Pseudomonas aeruginosa of 24h old culture with the percentage mortality and relative level of protection recorded for 4 weeks post – infection. The results demonstrated that the fish fed with treated diets showed increased in biochemical and haematological indices (P<0.05) compared with the control. The challenge infection showed an improvement from treated groups with percentage mortalities and relative level of protection highest in WL8 (3.33%, 90%) and OB2 (3.33%, 90%) and least (33.33%, 0%) in control respectively. The results suggest that walnut leaf residue at 1.5% inclusion for one month could be a potential, less expensive and promising dietary supplement that would positively affect growth, haematology and make C. gariepinus more resistant to Pseudomonas aeruginosa